Preparation method and application of tungsten-molybdenum carbide nanosheet heterojunction catalyst
By preparing tungsten molybdenum carbide nanocr tablet catalysts, the problem of high precious metal catalysts in electrolyte hydrogen hydrogen hydrogen hydrogen has achieved high -efficiency and stable alkaline electrolytic hydrogen hydrogen performance, and broke the performance limit of single metal carbide hydrogen.
Patent Information
- Application Number
- CN202411380170.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In the prior art, the precious metal catalyst used in the hydrogen production process of water electrolysis is expensive, and the performance of transition metal carbide electrocatalysts is still far from that of commercial Pt/C catalysts, making it difficult to achieve efficient electrolysis of aquatic hydrogen.
The preparation method of the heterogeneous catalyst catalyst of tungsten molybdenum carbide nanocrofin tablets is adopted. Through zinc, molybdenum acid and tungsten acid salt in the restore atmosphere, high -temperature carbonization is formed to form a catalyst with heterogeneous structures with heterogeneous structures, and acid Thermal treatment is removed to remove zinc metals and optimize the pore rate of catalysts.
This catalyst shows high -electricity catalytic activity and stability during alkaline electrolytic hydrogen hydrogen. The cathode is low, which can work stably at high current density for 30 hours, which significantly improves the performance of non -precious metal catalysts, close to or exceed the precious metal metal Performance of catalyst.
Smart Images

Figure CN118880388B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalysts, and in particular to a preparation method and application of a tungsten-molybdenum carbide nanosheet heterojunction catalyst. Background Art
[0002] Compared with traditional fossil hydrogen production processes, water electrolysis hydrogen production technology can not only couple renewable energy, but also obtain high purity hydrogen, low cost of subsequent separation and purification, and no secondary pollution in the entire hydrogen production process. Therefore, it is considered to be a relatively ideal green hydrogen production method. However, the voltage of industrial water electrolysis is generally between 1.8 and 2.0 V, which has a lot of room for improvement compared to the theoretical bias potential of 1.23 V. In order to reduce the actual required voltage, it is necessary to solve the high overpotential required for the cathode and anode reactions and the resistance problems in the water electrolysis system. At present, precious metal materials represented by Pt are usually used as catalysts in the cathode hydrogen evolution reaction. Their high cost is not conducive to the large-scale development of water electrolysis hydrogen production; how to develop non-precious metal-based catalysts to replace precious metal catalysts to achieve efficient water electrolysis hydrogen production is a major challenge for water electrolysis hydrogen production.
[0003] Among the non-precious metal catalysts reported so far, transition metal-based compounds such as transition metal sulfides, hydroxides, and carbides have been widely studied as substitutes for precious metal catalysts. Transition metal carbides, including Mo2C, W2C, and WC, have been reported many times for the electrolysis of water to produce hydrogen because of their d-band electronic structure similar to that of the precious metal Pt. For example, a Chinese patent document with publication number CN202210260511.1 discloses a tungsten carbide-tungsten sulfide composite catalytic material, in which the tungsten carbide-tungsten sulfide composite catalytic layer grows on the surface of a tungsten foil substrate layer. The composite catalytic material uses tungsten foil as a substrate and tungsten source. First, a tungsten trioxide film precursor is formed on the tungsten foil, and then a tungsten carbide-tungsten sulfide film with a vertical flake structure is synthesized in one step by chemical vapor deposition, showing relatively good hydrogen evolution performance. Another example is a Chinese patent document with publication number CN202210233979.1, which discloses a self-supporting tungsten-based composite material. The tungsten-based composite material uses tungsten foil as a substrate to synthesize tungsten carbide in situ, and then uses electrochemical deposition to construct Ni(OH)2 on the WC surface. The composite material can provide strong mechanical stability; Ni(OH)2 has moderate adsorption capacity for intermediate hydroxides and enhances the water dissociation step. At the same time, WC has a good ability to adsorb hydrogen. Under the synergistic effect of WC and Ni(OH)2, the hydrogen evolution capacity of the catalyst is greatly improved.
[0004] Although transition metal carbides have shown certain catalytic activity in hydrogen evolution by electrolysis of water, the performance of currently reported transition metal carbide electrocatalysts is still far behind that of commercial Pt / C and other precious metal catalysts. Therefore, by preparing a tungsten-molybdenum carbide nanosheet catalyst, it is possible to effectively balance its adsorption and desorption of water molecules and hydrogen intermediates. At the same time, the tungsten-molybdenum heterostructure can strengthen the electronic interaction between the active sites of tungsten and molybdenum metals, improve the electron utilization rate, and further improve the performance of hydrogen evolution by electrolysis of water, breaking the performance limitation of hydrogen evolution by single metal carbides and realizing the replacement of precious metal catalysts. Summary of the invention
[0005] In view of the problem that the intrinsic activity of hydrogen evolution in water electrolysis of single transition metal carbides is low in the prior art, the present invention provides a method for preparing a tungsten-molybdenum carbide nanosheet heterojunction catalyst. The prepared carbide nanosheet heterojunction catalyst exhibits excellent electrocatalytic activity for hydrogen evolution in alkaline water electrolysis and has good hydrogen evolution stability.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a tungsten-molybdenum carbide nanosheet heterojunction catalyst, comprising the following steps:
[0007] (1) Dissolving zinc salt in deionized water to obtain solution A, then dissolving molybdate, tungstate and N-methylimidazole in deionized water to obtain solution B, slowly and uniformly pouring solution A into solution B, continuously stirring and reacting at a constant temperature for a certain period of time, then centrifuging and washing, and drying to obtain a tungsten-molybdenum-zinc trimetallic organic framework;
[0008] (2) placing the tungsten-molybdenum-zinc trimetallic organic framework prepared in step (1) into a tubular furnace for calcination, and carbonizing at high temperature under a reducing atmosphere to generate a tungsten-molybdenum carbide nanosheet heterojunction catalyst containing zinc metal;
[0009] (3) The tungsten-molybdenum carbide nanosheet heterojunction catalyst containing zinc metal prepared in step (2) is subjected to thermal acid etching to remove the zinc metal, thereby obtaining the tungsten-molybdenum carbide nanosheet heterojunction catalyst.
[0010] Preferably, the molar ratio of the zinc salt to dimethylimidazole in step (1) is 1:1-4.
[0011] Preferably, in step (1), the molar ratio of zinc salt to tungstate to molybdate is 4:1-4:1-4, the reaction time is 12-24 h, and the reaction temperature is 20-25°C.
[0012] Preferably, in step (2), the calcination temperature is 700-1000° C., and the calcination time is 1-4 h.
[0013] Preferably, in step (2), the calcination atmosphere is a mixture of hydrogen and argon, with the hydrogen accounting for 3% to 20%.
[0014] Preferably, the acid concentration of the hot acid treatment in step (3) is 0.5 M to 3 M, the temperature of the hot acid treatment is 60 to 90 °C, and the hot acid treatment time is 10 to 20 h.
[0015] Preferably, the prepared tungsten-molybdenum carbide nanosheet heterojunction catalyst is used as a working electrode in an alkaline water electrolysis hydrogen evolution reaction.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) The tungsten-molybdenum carbide nanosheet heterojunction catalyst provided by the present invention has high electrocatalytic activity and stability in the process of hydrogen production by alkaline water electrolysis. -2 When the cathode overpotential is only about 92 mV, it can -2 The catalyst worked stably for 30 h without obvious potential decay, which increases the possibility of non-precious catalysts replacing precious metal catalysts.
[0018] (2) The tungsten-molybdenum carbide nanosheet heterojunction catalyst provided by the present invention uses two metal carbides to construct a heterostructure, and uses the electronic interaction of the tungsten-molybdenum metal sites to enhance the adsorption and desorption of hydrogen intermediates by the metal sites;
[0019] (3) The tungsten-molybdenum carbide nanosheet heterojunction catalyst provided by the present invention optimizes the mass transfer process between the catalyst and the electrolyte by regulating the porosity of the carbide surface, thereby increasing the active reaction area of the catalyst and improving the hydrogen evolution performance in alkaline water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope (SEM) image of the catalyst Mo2C / WC NS prepared in Example 1;
[0021] Figure 2 TEM image of the catalyst Mo2C / WC NS prepared in Example 1;
[0022] Figure 3 X-ray diffraction XRD pattern of the catalyst Mo2C / WC NS prepared in Example 1;
[0023] Figure 4 Polarization curves of the catalysts prepared in Example 1 and Comparative Examples 1 to 3 for hydrogen evolution in alkaline water electrolysis in application examples;
[0024] Figure 5 This is a constant current timing curve of hydrogen evolution in alkaline water electrolysis using the catalyst Mo2C / WC NS prepared in Example 1. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] like Figures 1 to 5 As shown, the embodiment of the present invention provides a method for preparing a tungsten-molybdenum carbide nanosheet heterojunction catalyst, comprising the following steps:
[0027] (1) Dissolve zinc salt in deionized water to obtain solution A, dissolve molybdate, tungstate and dimethylimidazole in deionized water to obtain solution B, control the molar ratio of zinc salt to dimethylimidazole to be 1:1-4, and the molar ratio of zinc salt to tungstate to molybdate to be 4:1-4:1-4, pour solution A into solution B, stir and mix to react, control the reaction time to be 12-24h at 20-25°C, and obtain a tungsten-molybdenum-zinc trimetallic organic framework. The zinc salt, molybdate or tungstate used are all soluble salts, zinc salts include nitrates, chlorides, acetates, sulfates and hydrates of cobalt, such as zinc nitrate, zinc chloride, zinc acetate, zinc sulfate, etc., molybdates include sodium molybdate, ammonium molybdate and hydrates thereof, etc., and tungstates include tungstates, ammonium tungstate and hydrates thereof.
[0028] (2) The tungsten-molybdenum-zinc trimetallic organic framework precursor prepared in step (1) is placed in a tubular furnace and calcined. The calcination temperature is controlled at 700-1000°C and the heating rate is controlled at 1-5°C min -1 The constant temperature calcination time is 1 to 4 hours. The calcination atmosphere is a mixture of hydrogen and argon, with hydrogen accounting for 3% to 20%. The organic skeleton is converted into a carbon skeleton after high-temperature calcination. Dimethylimidazole is used as a carbon source to form carbides with metal tungsten and metal molybdenum. Metallic zinc is reduced and precipitated, and finally a tungsten-molybdenum carbide nanosheet heterojunction catalyst containing zinc metal is obtained.
[0029] (3) The tungsten-molybdenum carbide nanosheet heterojunction catalyst containing zinc metal prepared in step (2) is heat-treated in an acid solution of a certain concentration, wherein the acid concentration is selected to be 0.5 M to 3 M, the temperature of the heat acid treatment is 60 to 90 °C, and the heat acid treatment time is 10 to 20 h, so as to remove the surface zinc ions and finally obtain a tungsten-molybdenum carbide nanosheet heterojunction catalyst.
[0030] The preparation principle is as follows: zinc ions can coordinate with dimethylimidazole, molybdate ions and tungstate ions, and the coordination between zinc ions and dimethylimidazole, molybdate ions and tungstate ions is used to react to form a tungsten-molybdenum-zinc trimetallic organic framework. The tungsten-molybdenum-zinc trimetallic organic framework is formed under a reducing atmosphere. The tungsten and molybdenum in the framework react with dimethylimidazole as a carbon source to form tungsten carbide and molybdenum carbide, and the zinc ions are reduced to form zinc metal particles. Then, through acid-heat treatment, the zinc metal particles in the carbide nanosheets are removed, the porosity of the catalyst surface is increased, and finally the preparation of tungsten-molybdenum carbide nanosheet heterojunction catalyst is realized.
[0031] The tungsten-molybdenum carbide nanosheet heterojunction catalyst prepared according to the preparation method can be represented by the chemical formula: Mo2C / WC NS, wherein Mo2C is molybdenum carbide; WC is tungsten carbide; and NS represents a nanosheet structure. The catalyst is a carbide with a heterogeneous structure composed of molybdenum carbide and tungsten carbide. After acid-heat treatment, the surface porosity increases. The prepared tungsten-molybdenum carbide nanosheet heterojunction catalyst can be used as a working electrode in alkaline water electrolysis hydrogen evolution reaction.
[0032] In the alkaline water electrolysis hydrogen evolution reaction, a standard three-electrode system is used, specifically, a glassy carbon electrode covered with a tungsten-molybdenum carbide nanosheet heterojunction catalyst provided by the present invention is used as a working electrode, a Hg / HgO electrode is used as a reference electrode, a carbon rod is used as a counter electrode, and a 1.0 M potassium hydroxide solution is used as an electrolyte.
[0033] Example 1
[0034] (1) Weigh 0.1 M zinc nitrate hexahydrate and dissolve it in 25 mL of deionized water to form solution A. Then weigh 0.1 M sodium tungstate, 0.1 M sodium molybdate, and 0.2 M dimethylimidazole and dissolve them in 25 mL of deionized water to form solution B. Slowly introduce solution A into solution B. The ratio of zinc salt to dimethylimidazole and tungstate to molybdate is selected because the ratio of zinc salt to dimethylimidazole has a significant effect on the formation of the organic skeleton. When the zinc salt concentration is too high, the zinc metal content in the generated organic skeleton is high, and particle agglomeration is prone to occur in the subsequent carbonization process. In addition, if the content of dimethylimidazole as a carbon source is too low, it will be unfavorable for the formation of molybdenum carbide and tungsten carbide; when the zinc salt concentration is too low, the zinc metal content in the generated organic skeleton is low, which is not conducive to the further coordination of zinc metal with tungstate and molybdate, resulting in a low content of tungsten and molybdenum ions in the precursor, resulting in a subsequent decrease in the content of molybdenum carbide and tungsten carbide, and a decrease in the number of catalytic active sites; and the concentration ratio of tungstate to molybdate will affect the subsequent formation of tungsten carbide and molybdenum carbide heterojunctions.
[0035] (2) The mixed solution was stirred at 25 °C for 20 h to generate a tungsten-molybdenum-zinc trimetallic organic framework precursor through reaction. The reason for choosing to carry out the reaction at a constant temperature of 25 °C is that the temperature and time of the reaction will affect the size of the organic framework. Adopting a constant moderate temperature and an appropriate reaction time is conducive to ensuring the uniformity of the size of the tungsten-molybdenum-zinc trimetallic organic framework precursor nanosheet structure.
[0036] (3) The tungsten-molybdenum-zinc trimetallic organic framework precursor was calcined in a tube furnace. The temperature of the tube furnace was set to 900 °C and the heating rate was controlled at 3 °C min -1 The reaction was carried out in a hydrogen / argon mixed gas (5% / 95%) atmosphere, and the heating time was 3 h at a constant temperature of 900 ℃. After the reaction was completed, it was cooled to room temperature to obtain a tungsten-molybdenum carbide nanosheet heterojunction catalyst containing zinc metal. Controlling the temperature and time of the carburization reaction is beneficial to the crystallinity of tungsten carbide and molybdenum carbide and the dispersibility of the active components. When the temperature is too low and the reaction time is short, the carburization effect is poor, and tungsten carbide and molybdenum carbide cannot be generated or the generated carbide has poor crystallinity. When the temperature is too high and the reaction time is too long, tungsten carbide and molybdenum carbide will easily agglomerate during the carburization process due to the high temperature, resulting in a decrease in the specific surface area of the generated carbide and poor dispersibility of the active components. Controlling the appropriate heating rate is to prevent the collapse of the structure when the organic skeleton is converted into a carbon skeleton due to excessive heating. The carbonization reaction was carried out in a hydrogen / argon mixed gas (5% / 95%) atmosphere because carbides are more easily formed and metallic zinc is more easily precipitated in a reducing atmosphere.
[0037] (4) The prepared tungsten-molybdenum carbide nanosheet heterojunction catalyst containing zinc metal was dissolved in 1 M H2SO4 solution; the reaction was stirred at 70 °C for 12 h, cooled to room temperature, washed three times by centrifugation with deionized water, and vacuum dried to obtain a tungsten-molybdenum carbide nanosheet heterojunction catalyst, which was recorded as Mo2C / WC NS. The acid concentration, acid treatment temperature and time were controlled to ensure the removal of zinc metal particles and increase the porosity and specific surface area of the catalyst. If the acid concentration and treatment temperature are too high or the treatment time is too long, the carbon structure may be destroyed, resulting in the dissolution of molybdenum carbide or tungsten carbide. If the temperature is too low, the zinc metal cannot be completely removed, which affects the specific surface area of the catalyst and leads to a decrease in hydrogen evolution activity.
[0038] The rich pore structure inside the catalyst is conducive to the contact reaction between the active sites and the electrolyte, which facilitates the subsequent hydrogen evolution reaction. At the same time, the heterogeneous structure composed of molybdenum carbide and tungsten carbide can further regulate the electronic environment around metal tungsten and molybdenum, which is conducive to balancing the binding and detachment of hydrogen with metal tungsten or molybdenum sites. Specifically, the rich pore structure can better transport water molecules to the catalyst surface, while the heterogeneous structure of molybdenum carbide and tungsten carbide can redistribute the electrons of the metal sites, thereby weakening the original metal site's excessive adsorption of hydrogen, making the adsorption and desorption of hydrogen intermediates more reasonable, and accelerating the kinetics of the hydrogen evolution reaction. The construction of this catalyst also optimizes the mass transfer and kinetics of the reaction process, and ultimately exhibits excellent hydrogen evolution performance.
[0039] The prepared tungsten-molybdenum carbide nanosheet heterojunction catalyst was observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The SEM results are shown in Figure 1 As shown in the TEM image Figure 2 As shown. Figure 1-Figure 2 It can be seen that the tungsten-molybdenum carbide nanosheet heterojunction catalyst presents a nanosheet structure with a thickness of tens of nanometers, and the carbide particles are dispersed in the sheet-like carbon skeleton. The X-ray diffraction XRD pattern of the tungsten-molybdenum carbide nanosheet heterojunction catalyst prepared in this embodiment is as follows: Figure 3 As shown, the characteristic peaks of tungsten carbide and molybdenum carbide can be seen in the catalyst, proving the successful synthesis of tungsten-molybdenum carbide nanosheet heterojunction catalyst.
[0040] Comparative Example 1
[0041] According to the process of Example 1, 0.1 M zinc nitrate hexahydrate was weighed and dissolved in 25 mL of deionized water to form solution A, and 0.1 M sodium tungstate, 0.1 M sodium molybdate and 0.2 M dimethylimidazole were weighed and dissolved in 25 mL of deionized water to form solution B. Solution A was slowly introduced into solution B, and the mixed solution was stirred at 25 °C for 20 h, centrifuged three times with deionized water, and dried to obtain a tungsten-molybdenum-zinc trimetallic organic framework precursor. The tungsten-molybdenum-zinc trimetallic organic framework precursor was placed in a tubular furnace for calcination, the temperature of the tubular furnace was set to 900 °C, and the heating rate was controlled to 3 °C min -1 The reaction atmosphere was a mixture of hydrogen and argon (5% / 95%), and the heating time was 3 h at a constant temperature of 900 ° C. After the reaction was completed, it was cooled to room temperature to obtain a tungsten-molybdenum carbide nanosheet heterojunction catalyst containing zinc metal, recorded as Zn@Mo2C / WC NS. Without subsequent thermal acid treatment, the catalyst surface contained zinc metal nanoparticles with small pores, which was compared to highlight the tungsten-molybdenum carbide nanosheet heterojunction catalyst prepared in Example 1, proving the role of the high-porosity surface in promoting the hydrogen evolution process of water electrolysis.
[0042] Comparative Example 2
[0043] According to the process of Example 1, 0.1 M zinc nitrate hexahydrate was weighed and dissolved in 25 mL of deionized water to form solution A, and 0.1 M sodium tungstate and 0.2 M dimethylimidazole were weighed and dissolved in 25 mL of deionized water to form solution B. Solution A was slowly introduced into solution B, and the mixed solution was stirred at 25 °C for 20 h, centrifuged three times with deionized water, and dried to obtain a tungsten-zinc organic framework precursor. The tungsten-zinc organic framework precursor was placed in a tubular furnace for calcination, and the temperature of the tubular furnace was set to 900 °C, and the heating rate was controlled to 3 °C min -1 The reaction atmosphere was a mixture of hydrogen and argon (5% / 95%), and the heating time was 3 hours at a constant temperature of 900°C. After the reaction was completed, the mixture was cooled to room temperature to obtain a tungsten carbide nanosheet heterojunction catalyst containing zinc metal. The prepared tungsten carbide nanosheet catalyst containing zinc metal was dissolved in a 1 M H2SO4 solution; the reaction was stirred at 70°C for 12 hours, cooled to room temperature, centrifuged and washed three times with deionized water, and vacuum dried to obtain a tungsten carbide nanosheet catalyst, which was recorded as WC NS. Single-component tungsten carbide was synthesized to compare the effect of the heterostructure composed of molybdenum carbide and tungsten carbide in the composite carbide component on the hydrogen evolution performance.
[0044] Comparative Example 3
[0045] According to the process of Example 1, 0.1 M zinc nitrate hexahydrate was weighed and dissolved in 25 mL of deionized water to form solution A, and 0.1 M molybdenum tungstate and 0.2 M dimethylimidazole were weighed and dissolved in 25 mL of deionized water to form solution B. Solution A was slowly introduced into solution B, and the mixed solution was stirred at 25 ° C for 20 h, centrifuged three times with deionized water, and dried to obtain a molybdenum zinc organic framework precursor. The molybdenum zinc organic framework precursor was placed in a tubular furnace for calcination, and the temperature of the tubular furnace was set to 900 ° C, and the heating rate was controlled to 3 ° C min -1 The reaction atmosphere was a mixture of hydrogen and argon (5% / 95%), and the heating time was 3 hours at a constant temperature of 900°C. After the reaction was completed, the mixture was cooled to room temperature to obtain a heterojunction catalyst of molybdenum carbide nanosheets containing zinc metal. The prepared molybdenum carbide nanosheet catalyst containing zinc metal was dissolved in a 1 M H2SO4 solution; the reaction was stirred at 70°C for 12 hours, cooled to room temperature, centrifuged and washed three times with deionized water, and vacuum dried to obtain a molybdenum carbide nanosheet catalyst, which was recorded as Mo2C NS. Single-component molybdenum carbide was synthesized to compare the effect of the heterostructure composed of molybdenum carbide and tungsten carbide in the composite carbide component on the hydrogen evolution performance.
[0046] Application Examples
[0047] (1) A three-electrode system was used, with the glassy carbon electrode covered with the catalyst prepared in Example 1 or Comparative Examples 1-3 as the working electrode, the counter electrode as a carbon rod, the reference electrode as a saturated Hg / HgO electrode, and the electrolyte as 1.0 M KOH;
[0048] (2) CV activation: Shanghai Chenhua CHI 760E electrochemical workstation was used. Argon was introduced into the electrolyte for 0.5 h before testing. The CV program was used with a test range of 0 to -0.8 V vs. RHE and a scan rate of 0.05 V s -1 After 50 cycles, the electrode reaches a stable state.
[0049] The catalysts prepared in Example 1 and Comparative Examples 1-3 were subjected to linear sweep voltammetry (LSV) test.
[0050] After activation, the program was switched to the LSV program with a test interval of 0 to -0.8 V vs. RHE, a scan rate of 5 mV / s, and an overpotential of 0 V and 10 mA cm relative to the reversible hydrogen electrode. -2 The potential difference is measured under Figure 4 As shown, the polarization curves of the Mo2C / WC NS and Zn@Mo2C / WC NS, Mo2C NS and WC NS provided in this embodiment for the hydrogen evolution reaction in the electrolysis of water in 1.0 M KOH solution are shown in FIG. Figure 4 As shown, from Figure 4 It can be seen that in an alkaline environment, the overpotential of the Mo2C / WC NS catalyst is about 92 mV, which is significantly better than single-component tungsten carbide and molybdenum carbide and tungsten molybdenum carbide containing zinc metal that has not been treated with thermal acid etching. It proves that the optimization of heterogeneous structure and pore structure has a synergistic effect on hydrogen evolution in water electrolysis.
[0051] The catalyst prepared in Example 1 was tested for stability.
[0052] After CV activation, the program was switched to ISTEP and the current was set to 0.0007 A, i.e., the current density was 10 mA cm -2 , the running time is set to 30 h. Figure 5 As shown, the potential of the tungsten-molybdenum carbide heterojunction catalyst is basically stable near the initial potential of 92 mV and does not change, proving that it has good stability for hydrogen evolution in alkaline water electrolysis.
[0053] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a tungsten-molybdenum carbide nanosheet heterojunction catalyst, characterized in that: The steps include: (1) dissolving zinc salt in deionized water to obtain solution A, and then dissolving molybdate, tungstate and 2-methylimidazole in deionized water to obtain solution B, wherein the molar ratio of zinc salt to 2-methylimidazole is 1:1-4, and the molar ratio of zinc salt to tungstate to molybdate is 4:1-4:1-4, and solution A is slowly and uniformly poured into solution B, and the reaction time is controlled at 20-25° C. for 12-24 hours to obtain a tungsten-molybdenum-zinc trimetallic organic framework; (2) placing the tungsten-molybdenum-zinc trimetallic organic framework prepared in step (1) into a tubular furnace for calcining at 700-1000° C. for 1-4 h, and carbonizing at high temperature in a reducing atmosphere to generate a tungsten-molybdenum carbide nanosheet heterojunction catalyst containing zinc metal; (3) The tungsten-molybdenum carbide nanosheet heterojunction catalyst containing zinc metal prepared in step (2) is subjected to thermal acid etching to remove the zinc metal, thereby obtaining the tungsten-molybdenum carbide nanosheet heterojunction catalyst.
2. The method for preparing the tungsten-molybdenum carbide nanosheet heterojunction catalyst according to claim 1, characterized in that: In step (2), the calcination atmosphere is a mixture of hydrogen and argon, with the hydrogen accounting for 3% to 20%.
3. The method for preparing the tungsten-molybdenum carbide nanosheet heterojunction catalyst according to claim 1, characterized in that: In step (3), the acid concentration of the hot acid treatment is 0.5M to 3.0M, the temperature of the hot acid treatment is 60 to 90°C, and the hot acid treatment time is 10 to 20 hours.
Citation Information
Patent Citations
Tungsten-based composite material and preparation method and application thereof
CN115852386A
A tungsten carbide-tungsten sulfide composite catalytic material and its preparation method and application
CN115852387B